In situ power-cadence relationship for 2-, 5-, and 20-minute duration: A proof of concept in under-19 cyclists - Bertron, Y.; Bowen, M.; Samozino, P.; Leo, P.; Pacot, A.; Quiclet, J.-B.; Hintzy, F.; Morel, B. (International Journal of Sports Physiology and Performance, 2024)
Background The force-velocity relationship suggests that maximal power (Pmax) can only be produced in optimal torque (Topt) and cadence (Copt). However, the cadence at which mean maximal power (MMP) is produced has never been studied. This study aimed to determine the individual MMP-cadence relationship from in situ data.